12
$\begingroup$

Is there a better (more direct or intuitive) proof for this proposition than I have come up with below? I am not sure whether it could be simiplified:

Let $G$ be a group with $H \leq G$. Then $K = \bigcap_{g \in G} gHg^{-1}$ is normal in $G$.

Let $a \in K$. Then $a \in gHg^{-1}$ for all $g \in G$. Therefore for all $g_1,g \in G$, $g_1ag_1^{-1} \in g_1gHg^{-1}g_1^{-1} = (g_1g)H(g_1g)^{-1}$ and so $g_1ag_1^{-1} \in K$ since $g_1g \in G$. Then $K$ is normal in $G$.

$\endgroup$
5
  • 1
    $\begingroup$ That's essentially correct, provided you observe that $G=\{g_1g\;;\;g\in G\}$. You have only noticed $\supseteq $. So it would maybe be slightly better to say: $g_1ag_1^{-1}\in g_1(g_1^{-1}gH(g_1^{-1}g)^{-1})g_1^{-1}=gHg^{-1}$ for every $g\in G$. Thus $g_1ag_1^{-1}\in K$ for every $g_1\in G$ and every $a\in K$. $\endgroup$ – Julien Apr 22 '13 at 19:23
  • 2
    $\begingroup$ For an element-free argument, you can also write $gKg^{-1}=g\left(\bigcap_{g'\in G}g'Hg'^{-1}\right)g^{-1}=\bigcap_{g'\in G}gg'Hg'^{-1}g^{-1}=\bigcap_{g'\in G}gg'H(gg')^{-1}=\bigcap_{g'\in G}g'Hg'^{-1}=K$. $\endgroup$ – Julien Apr 22 '13 at 19:26
  • 2
    $\begingroup$ You should also notice that $K$ is the largest (in terms of order) possible normal subgroup of $G$ that is also a subgroup of $H$ (and all of $H$'s conjugates). From a lattice prospective, that's kinda special. $\endgroup$ – Mud Apr 22 '13 at 19:33
  • $\begingroup$ @julien I think is there an 'element-free' argument is what I meant, but I didn't know how to say it! $\endgroup$ – user50229 Apr 22 '13 at 19:39
  • $\begingroup$ @julien If you write your element-free argument as an answer I would be happy to accept. $\endgroup$ – user50229 May 3 '13 at 13:04
12
$\begingroup$

For every $g\in G$, we have $$ gKg^{-1}=g\left(\bigcap_{g'\in G} g'Hg'^{-1}\right)g^{-1}=\bigcap_{g'\in G} gg'Hg'^{-1}g^{-1}=\bigcap_{g'\in G} gg'H(gg')^{-1} $$ $$ =\bigcap_{g'\in G}g'Hg'^{-1}=K. $$ Note that the less trivial step is the second one. It is due to the fact that $x\longmapsto gxg^{-1}$ is injective for $\supseteq$. The inclusion $\subseteq$ is straightforward.

$\endgroup$
2
  • $\begingroup$ Can you explain how the second equality makes sense? How do we put the $g$ and $g^{-1}$ inside the intersection? $\endgroup$ – BSplitter Mar 13 '17 at 3:56
  • $\begingroup$ While showing equality in the second step. I went as follows: Let $k \in \bigcap_{g'\in G} gg'Hg'^{-1}g^{-1}$, \rightarrow $k=gwg^{-1}$ where $w\in g'Hg'^{-1}$ for all $g' \in G$ \rightarrow $w\in \bigcap_{g' \in G}$ \rightarrow $k=gwg^{-1} \in g\left(\bigcap_{g'\in G} g'Hg'^{-1}\right)g^{-1}$. And inclusion $\subseteq$ is straightforward. Hence equality holds. Am I correct? Where am I using the fact that $x \mapsto gxg^{-1}$ is injective? $\endgroup$ – Saikat Oct 15 '20 at 6:22
7
$\begingroup$

This is not much different in essence, but emphasizes the other important definition of normal subgroup as kernel of homomorphism.

Consider the action of $G$ on the cosets of $H$ given by multiplication. This is a homomorphism $\phi$ from $G$ to the symmetric group on the set $G/H = \{ gH : g \in G \} = \{ \{ gh: h \in H \} : g \in G \}$. As such, it has a kernel $K$, those $k$ such that $kgH = gH$ for all $g \in G$. This is precisely the $k$ such that $kg = gh_g$ for some $h_g \in G$ dependent on $g$, that is $k = gh_g g^{-1} \in gHg^{-1}$. In other words, $\bigcap_{g\in G} gHg^{-1} = \ker(\phi)$.

$\endgroup$
1
$\begingroup$

Let $ a \in K$ this implies $ a \in qHq^{-1}\;\forall q \\Let\;q = g^{-1}r \;\;(notice \;there\;is\;no\;restriction\;on\;g\;or\;r) \\then \; a\in (g^{-1}r )H(g^{-1}r )^{-1} \\a\in (g^{-1}r )H(r^{-1}g) \\gag^{-1}\in rHr^{-1}$

Because r and g donot have any restriction, we can take any r and g, or, every g and r to give:

$\forall g \; \forall r \; gag^{-1} \in rHr^{-1}\\ \forall g \; gag^{-1} \in \cap_{r}\ rHr^{-1}$

$\endgroup$
0
$\begingroup$

Let $n\in K, g\in G$. For any $b\in G,$ $n\in K=\bigcap\limits_{a\in G}a^{-1}Ha\subseteq (bg)^{-1}Hbg$. Then $n=(bg)^{-1}h(bg)$ for some $h\in H.$ Then $gng^{-1}=g(bg)^{-1}h(bg)g^{-1}=b^{-1}hb\in b^{-1}Hb$ for any $b\in G$. So $gng^{-1}\in \bigcap\limits_{a\in G}a^{-1}Ha=K$.

$\endgroup$
0
$\begingroup$

Your $K$ is the kernel of the homomorphism $$G \to \mathrm{Sym}(G/H),\quad \tilde g \mapsto (gH \mapsto \tilde g g H),$$ hence normal.

$\endgroup$
1
  • $\begingroup$ This answer was given already $\endgroup$ – user50229 Oct 17 '20 at 11:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.